Analysis and Treatment of Floating Slab Track Bed Defects in Shanghai Rail Transit - QU Feng (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] Due to its excellent vibration and noise reduction performance, the floating slab track bed is widely used in urban rail transit. However, with the increasing service time, issues related to the deteriorating conditions of floating slab track gradually emerge, presenting significant challenges for the maintenance and management of floating slab track structure. It is therefore necessary to analyze the floating slab track bed defects and summarize corresponding treatment measures to provide references for floating slabs maintenance work. [Method] Taking the floating slab track bed maintenance work across the entire Shanghai rail transit network as the context, the working principles and structural characteristics of the floating slab are analyzed. The main types of defects, the impact characteristics, and causes of floating slab track structure within Shanghai rail transit line network are identified. A set of treatment measures such as precise load force adjustment, void filling, and replacement of failed components are proposed. Taking a rail transit line in Shanghai as example, its floating slab track defect treatment steps are analyzed concretely. [Result & Conclusion] Through various measures such as online monitoring, precise load force adjustment, and maintenance and component replacement, the service condition of floating slabs can be ensured. It is recommended to strengthen routine inspections in key sections, enhance the application of online monitoring technologies, and establish a big data platform to drive optimization in track structure design. This will enable the upgrade of preventive maintenance strategies and lifecycle cost control for floating slab track, comprehensively improving the proactivity and scientific basis of track structure operation and maintenance.